KONDISI EKOSISTEM TERUMBU KARANG DI PERAIRAN PULAU TUNDA, BANTEN - Husnul Amalia; Gema Ikrar Muhammad (Universitas Cokroaminoto Palopo, 2026)
A study on the condition of coral reef ecosystems was conducted at four observation sites in the waters of Tunda Island, Banten Province. This research aimed to collect data on the percentage cover of live hard corals, the number of coral colonies, the relative dominance of corals based on percentage cover and colony abundance, coral distribution, and the number and composition of coral species in the waters of Tunda Island. The study was designed to determine the percentage of coral cover and the overall condition of the coral reef ecosystem. The observation method used was the Line Intercept Transect method. The results showed that the condition of the coral reef ecosystem at the study sites, based on live hard coral cover, was categorized as moderate. The site with the highest coral cover was Timur (37.9%), while the lowest was Utara 1 (26%). A total of eight coral species were recorded, representing four families and six genera. Three species had the widest distribution: Goniastrea sp., Acropora nobilis, and Montipora capricornis. The species that most dominated based on percentage cover was Goniastrea sp. (relative dominance based on cover, DRt = 37.01%). This species also dominated in terms of colony abundance (relative dominance based on colonies, DRk = 70.9%). The highest similarity index was found between Utara 1 and Utara 3 (93%). Timur had the highest species richness, with seven species recorded. Utara 1 had the highest heterogeneity index (H’ = 1.62) and also the highest evenness index (J = 0.90).